The observability of the ionospheric Alfven resonances in Antarctica over the complete solar cycle and the splitting effect - N.A. Baru; A.V. Koloskov; Yu.M. Yampolski; R.A. Rahmatulin; A.Yu. Pashinin (Ukrainian Antarctic Journal, 2014)
The dependence of the characteristics of the ionospheric Alfven resonance (IAR) signals from the geomagnetic and solar activity are investigated over an eleven-year solar cycle on the grounds of the analysis of the continuous data of the natural VLF-ELF noise that is registered at Ukrainian Antarctic Station (UAS) Akademik Vernadky from 2002 till 2013. Significant anticorrelation between the observability of the resonance modes and the Wolf numbers and local K-indexes that is measured at UAS is found. The diurnal and seasonal regularities of the observability of the new effect, the splitting of the lower resonance modes, and its dependence form the phase of the eleven-year solar cycle are investigated using the data of IAR observations at UAS and Sayan Solar observatory (Mondy, Russia). The morphological features of the behaviour of the splitting magnitude are analyzed and its main stages as evolution, stationary section and relaxation are allocated. Possible mechanisms of the appearance of splitting effect are offered.